A classroom-based study on the effects of WCF on accuracy in pen-and-paper versus computer-mediated collaborative writing - González-Cruz, Belén; Cerezo, Lourdes; Nicolás-Conesa, Florentina (Studies in Second Language Learning and Teaching, 2022)
This study compared the effects of computer-mediated (CM) versus pen-and-paper (P&P) writing on written accuracy and feedback processing in tasks written and rewritten collaboratively following a pedagogical treatment in two intact authentic classrooms. The study involved 32 secondary education low-proficiency English-as-a-foreign-language (EFL) learners writing two descriptive texts collaboratively and receiving in-class training in the identification and correction of grammatical, lexical, and mechanical errors. Participants were provided with unfocused direct error correction (EC). Error logs were used to facilitate noticing of teacher corrections (i.e., feedback processing). Dyads were required to rewrite their texts for evidence of feedback uptake. Results indicate that writing collaboratively on the computer with the availability of the Internet contributes to increased grammatical and lexical accuracy. No differences were found between writing environments regarding feedback processing or accuracy of rewritten texts.